Systematic narrowing of ZIF-8 apertures via controlled 2-ethylimidazole doping for hydrogen/carbon dioxide separation - Yang, Lee; Park, Sunghwan; Han, Wong Zhong; Abdul Razak, Musab; Zhen, Lee Yong; Faires, Muhammed; Omar, Rozita; Choong, Thomas Shean Yeaw; Rohani, Rosiah; Abdul Hamid, Mohamad Rezi (Springer, 2024)
Sodalite (SOD) zeolitic-imidazolate frameworks (ZIFs) with uniform angstrom scale apertures can offer high gas sieving ability for separation applications. Fixed apertures of ZIFs can effectively separate specific gas pair but may not be able to provide similar level of separation for larger or smaller gas pairs. Multivariate (i.e., mixed-linker) ZIFs with controlled linker incorporation can provide desired aperture tuning but difficult to synthesize especially when incorporating linkers that would normally form different structures. Herein, we report a systematic narrowing of SOD ZIF-8 by partially replacing 2-methylimidazole (mIm) linkers of ZIF-8 with 2-ethylimidazole (eIm) via delayed linker addition (DLA) method. Percentages of eIm in the hybrid frameworks were determined to be around 14.3%, 9.1%, and 5.1% for ZIF-8 nuclei formed in 5, 12.5, and 20 min, respectively. Ethyl moiety of eIm restricts framework flexibility of the hybrid ZIF-8, shifts ZIF-8 gate-opening pressure to higher value, and eventually diminishes the gate-opening effect. Polysulfone (PSF)-based mixed-matrix membranes utilizing eIm-doped ZIF-8 as fillers displayed slight reduction in CO2 permeability (18.56 Barrer to 14.85 Barrer) which result in H2/CO2 ideal selectivity improvement. DLA method is expected to work well for other imidazole-based linkers and can perhaps be used to synthesize mixed-linker of other SOD ZIFs.